Analisis Faktor-Faktor Yang Memengaruhi Ekspor Ikan Tuna Beku Indonesia - Veronica do Carmo da Silva; Bayu Krisnamurthi; Harmini (Forum Agribisnis, 2023)
This study aims to analyze the factors affecting Indonesia's frozen tuna exports. The data used in this study is panel data from 2005 to 2020 to export destination countries, such as Thailand, Japan, China and Vietnam. The method used in this research is panel data regression with a gravity model approach. According to the gravity model analisys the variables that have a positive and significant effect are importer population, exchange rate, coverage ratio SPS and TBT, while export price have a negative and significant effect. Otherwise, the variables that have no significant effect was GDPpercapita importer, economic distance and dummy variable impor tariffs. Based on these results, Indonesia needs to focus on increasing frozen tuna export to Thailand, China, Jepang and Vietnam because it will provide great benefits for Indonesia because Indonesia has been able to meet the criteria of standard and regulations imposed by importing countries, besides frozen tuna has high demand, highly export price and than exchange rate is also high in these countries. Furthermore the government always colaborate with producers (exporter) in producing frozen tuna to maintaining the quality of frozen tuna to be maintaned and exsist in export destination countries.